General Theory and Global Criminology: Childhood Environments, Problem Behaviors, and a Focus on Prevention - Gottfredson, Michael R. (Asian journal of criminology, 2018)
General theories of crime and delinquency are tested in part by their ability to explain the empirical findings of cross-national research. Systematic research using comparable survey methods provides a rich body of data from many countries and settings that inform such tests. There are several aspects of the general theory proposed by Gottfredson and Hirschi (1990) that facilitate the idea of global criminology which, coupled with this growing research literature, support the idea of general theories of crime. These include use of a “crime-free” definition for dependent variables, disciplinary-free assumptions about human nature, appreciating the distinction between propensities and events in crime theory, incorporating the burgeoning empirical literature from many disciplines stressing the importance of childhood environments and self-control, and focusing on recent successful prevention efforts. A set of research needs stimulated by modern global criminology are also proposed.